HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KEMAMPUAN TENDANGAN DOLLYO CHAGI PADA SISWA EKSTRAKURIKULER SMA NEGERI 1 BANGKO PUSAKO - Firmasnyah '; Saripin '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of the problem in this research is not optimal yet dollyo chagi ability extracurricular students SMAN 1 Bangko Pusako. This problem can be seen from the observation of researchers during training and exhibition, it is suspected because of explosive power legs muscles. Therefore, the purpose of this study was to determine whether there is a corelation of explosive power legs muscles with dollyo chagi ablility in extracurricular students of SMAN 1 Bangko Pusako. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is a explosive power legs muscles while the dependent variable (Y) is the dollyo chagi ability. The research data was obtained from the vertical jump test, and dollyo chagi kick test. Based on the research results can be concluded as follows: "there is a significant corelation between explosive power legs muscles and dollyo chagi ability taekwondo athletes in extracurricular students SMA Negeri 1 Bangko Pusako. It is characterized by the results obtained by the count r = 0.81> r table = 0.361, while th (5.1660)> t (1,76).Keywords : Explosive Power Legs Muscles, Dollyo Chagi